Efficacy and safety of lactoferrin based cream (SiraciltTM acne) in the treatment of patients with mild to moderate acne vulgaris – a randomized, comparative and pilot study - Shah, Harsh J.; Pariyani, Jacky K.; Shinde, Kalyani V. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: This pilot study was planned to evaluate the efficacy and safety of Siracilt™ Acne (lactoferrin, azelaic acid, and niacinamide) cream and compare it with azelaic acid cream and clindamycin gel in the treatment of patients with mild to moderate acne vulgaris. Methods: This study was a randomized, open-label active controlled, parallel group clinical trial. A total of 80 patients with mild to moderate acne vulgaris [investigator global assessment (IGA) score, 2 or 3] were randomized to receive Siracilt™ Acne cream, azelaic acid 10% cream, azelaic acid 20% cream, and clindamycin 1% gel for 4 weeks. The primary endpoint was the proportion of patients who achieved treatment success (IGA score, 0 or 1 and/or at least a 2-point reduction in IGA score) after 4 weeks. Secondary efficacy endpoints included a percentage reduction of total lesions and a change in total, inflammatory, and non-inflammatory lesions after 4 weeks. Results: After 4 weeks, the proportion of patients achieving treatment success in the Siracilt™ Acne group was 65%; while it was 0%, 10%, and 0% in azelaic acid 10%, azelaic acid 20%, and clindamycin 1% groups, respectively. The percentage reduction in the number of total acne lesions after 4 weeks was 62.1%, 27.2%, 46.6%, and 25.1% with Siracilt™ Acne cream, azelaic acid 10% cream, azelaic acid 20% cream, and clindamycin 1% gel, respectively. Similar results were observed for change in total, inflammatory, and non-inflammatory lesions after 4 weeks. Overall, the treatments were safe and well tolerated. Conclusions: In conclusion, Siracilt™ Acne cream demonstrated superior efficacy compared to azelaic acid and clindamycin in the treatment of mild to moderate acne vulgaris.